2009
DOI: 10.1161/circresaha.108.193102
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MiR-199a Derepresses Hypoxia-Inducible Factor-1α and Sirtuin 1 and Recapitulates Hypoxia Preconditioning in Cardiac Myocytes

Abstract: MicroRNAs are posttranscriptional gene regulators that are differentially expressed during various diseases and have been implicated in the underlying pathogenesis. We report here that miR-199a is acutely downregulated in cardiac myocytes on a decline in oxygen tension. This reduction is required for the rapid upregulation of its target, hypoxia-inducible factor (Hif)-1α. Replenishing miR-199a during hypoxia inhibits Hif-1α expression and its stabilization of p53 and, thus, reduces apoptosis. On the other hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
431
2
4

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(449 citation statements)
references
References 39 publications
12
431
2
4
Order By: Relevance
“…Moreover, our study also showed that miR-181a decreases SIRT1 protein levels in mouse liver. Previous studies have shown that SIRT1 can be regulated by multiple miRNAs, such as miR-9, miR-22, miR-34a, miR-132, miR-199a and miR-217 in some different biological processes [27,[30][31][32]. In our experiment, we similarly observed the inhibitory effect of these miRNAs.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, our study also showed that miR-181a decreases SIRT1 protein levels in mouse liver. Previous studies have shown that SIRT1 can be regulated by multiple miRNAs, such as miR-9, miR-22, miR-34a, miR-132, miR-199a and miR-217 in some different biological processes [27,[30][31][32]. In our experiment, we similarly observed the inhibitory effect of these miRNAs.…”
Section: Discussionsupporting
confidence: 82%
“…Previous work had identified several hypoxia-regulated mRNAs, such as HIF1a and SIRT1, as being direct miR-199a-5p targets in cardiomyocytes. 32 Emphasis was placed on the WNT signaling factors WNT2, FZD4, and JAG1, as these three genes have been shown to have an important role in muscle stem cell Percentage of zebrafish with noticeable pericardial edema WT or Tg(mylz2-miR-199a-5p) Tg fish offspring at 5 dpf. Scale bars denote percentage error of the mean, and samples were analyzed in three separate mating cohorts Figure 7 MiR-199a-5p targets several components of the WNT signaling pathway in muscle.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that inducible miR-199a-5p arrests cell proliferation and contributes to cell death (7,8,26,27). Our group and others have previously reported that miR-199a-5p regulates cellular detoxifying systems by targeting multidrug resistance-associated protein 1 (6) and CD44 (12).…”
Section: Discussionmentioning
confidence: 95%
“…It is expressed in a variety of organs including the brain (6), liver (9), stomach (10), ovarian tissue (11,12), testicular tissue (13), and the cardiovascular system, such as in cardiomyocytes (7,8) and endothelial cells (14,15). Recent evidence revealed that miR-199a-5p plays a critical role in attenuating cell migration and in limiting cancer cell metastasis by targeting receptor tyrosine kinase Discoidin domain receptor-1 (9), Axl (16), and anti-adhesive transmembrane glycoprotein podocalyxin-like protein 1 (13).…”
mentioning
confidence: 99%